Personnel development in the ministry of industry and commerce, LAO People’s Democratic Republic . - Keobounphanh, Khanlasy (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objectives of this study were (1) Factors affecting Personnel Development in the Ministry of Industry and Commerce; (2) Problems of Personnel development; and (3) The model of Personnel development in the Ministry of Industry and Commerce. This research forms were Mixed Research using 1) Qualitative Research including document research and In-depth interviews with 4 senior executives, the tool used was a structured interview and group discussions with 4 middle level executives and 4 operational levels and Quantitative Research by using questionnaires as a tool to inquire personnel of the Ministry of Industry and Trade, which were a total population of 420 people. Statistics such as multiple regression analysis, frequency, percentage, mean, standard deviation and content analysis Major Findings : On the factors affecting Personnel Development in the Ministry of Industry and Commerce it were found that with statistical significance at 0.01 level namely, leadership, curriculum, personnel development Personnel development evaluation and knowledge of information technology capabilities. The personnel development policy and administrative resources no statistical significance. Can create predictions, predict the level of personnel development success. The prediction equation in the form of raw score: Yˆ = 0.662 + 0.192 (Leadership) + 0.120 (Personnel Development Program) + 0.091 (Information Technology Competency) + 0.294 (Personnel Development Evaluation) and The prediction equation in the form of standard score: Zˆ = 0.247 (Leadership) + 0.139 (Personnel Development Program) + 0.104 (Information Technology Competency) + 0.340 (Personnel Development Evaluation) (2) Problems of Personnel development were found that problems and obstacles of personnel development include, Budget constraints, Lack of coordination, The capacity is limited, There were no courses in international trade and industry law, The payroll of personnel were not consistent with the cost of living. Inspection restrictions, The creation of information technology networks were not covered in the backcountry and Personnel still lack knowledge and experience in working with foreigners or international organizations. (3) The model of Personnel development in the Ministry of Industry and Commerce are 4 sides 1) Leadership 2) Curriculum Personnel Development 3) Evaluation and 4) Information Technology and The success of personnel development has components 7 sides 1) Personnel planning 2) Development and training 3) Compensation 4) Information technology 5) Promoting roles of personnel 6) Working environment and 7) Cooperation with international. Article history : Received 02 February 2019 Revised 05 March 2019 Accepted 7 March 2019 SIMILARITY INDEX = 1.39